Novel KRIT1/CCM1 and MGC4607/CCM2 Gene Variants in Chinese Families With Cerebral Cavernous Malformations - Wang, Kang; Wu, Dengchang; Zhang, Baorong; Zhao, Guohua (Frontiers in Neurology, 2018)
Familial cerebral cavernous malformations (CCMs) are autosomal dominant disorders characterized by hemorrhagic strokes, recurrent headache, epilepsy, and focal neurological deficits. Genetic variants in KRIT1/CCM1, MGC4607/CCM2, and PDCD10/CCM3 genes contribute to CCMs. The clinical information of two Chinese families with CCMs was collected. MRI and video-electroencephalography were performed. Genetic variants of CCM1, CCM2, and CCM3 genes were investigated by exome sequencing. The patients were presented with recurrent epilepsy or headache. Susceptibility-weighted images of brains showed many dark dots, while video-electroencephalography revealed many spikes from multiple brain regions of patients. Exome sequencing revealed a novel CCM1 genetic variant (c.1599_1601TGAdel, p.Asp533del) and a novel CCM2 genetic variant (c.773delA, p.K258fsX34) in Family one and Family two, respectively; cosegregation existed in these two families. The two family members presented typical CCMs symptoms. These two novel genetic variants in CCM1 and CCM2 genes were the causation of CCM in the two Chinese families, and our data enriched the genetic variant spectrum of CCM genes.